Assessing the factors associated with body image perception and quality of life of Palestinian women undergoing breast cancer treatment: a cross-sectional study - Bayan Omari; Sabila Abu Riash; Atef Arfat; Riad Amer; Sultan Mosleh; Ramzi Shawahna (BMC, 2024)
Abstract Background Worldwide, breast cancer has replaced lung cancer and has become the most commonly diagnosed malignancy. Breast cancer poses a significant burden on the health and quality of life of women and can lead to substantial physical burdens and significant psychological problems, including distress, anxiety, depression, and sexuality-related issues, including negative body image. This study was conducted to assess how women diagnosed with, treated, and/or receiving treatment for breast cancer perceived their body image. Methods A cross-sectional study design was used to assess body image perceptions among Palestinian women diagnosed with breast cancer. The study was conducted in four different hospitals located in the West Bank of Palestine where women with breast cancer received their treatments or visited for follow-up care in the period between November 2023 and March 2024. An interviewer-administered questionnaire was used to collect the data. Body perception was assessed using the body image self-rating questionnaire for breast cancer (BISQ-BC). Results In this study, 376 women with breast cancer completed the interviewer-administered questionnaire (response rate = 75.2%. The mean age of the women was 44.0 ± 5.3 years. Of the women, 74.7% agreed or strongly agreed that they cared about their body image. On the other hand, 43.1% of the women were not satisfied with their body image and 58.8% did not think that their body image was attractive. Multiple linear regression showed that younger age, employment status, living in cities, marital status, educational level, presence of comorbidities, and longer time passes since diagnosis with breast cancer were associated with the different aspects of body image perception and behavior. Conclusion The findings of this study indicated that Palestinian women with breast cancer were concerned about their body image. The findings also indicated that breast cancer and its treatment posed a significant burden on the physical and psychosocial well-being of the affected women and impacted the different dimensions of their lives, including their perceptions of their body image. Patients with significant physical and body image changes might benefit from reconstructive surgeries, psychosocial support, cognitive behavioral therapy, and nutritional, and physical activity interventions.